Two Compartment Evaluation of Liver Grafts During Acellular Room Temperature Machine Perfusion (acRTMP) in a Rat Liver Transplant Model - Abraham, Nader; Zhang, Min; Cray, Paul; Gao, Qimeng; Samy, Kannan P.; Neill, Ryan; Cywinska, Greta; Migaly, JonCarlo; Kahan, Riley; Pontula, Arya; Halpern, Samantha E.; Rush, Caroline; et al. (Frontiers in Medicine, 2022)
Background. Subnormothermic machine perfusion (SNMP) of liver grafts is currently less clinically developed than normothermic and hypothermic approaches, but may have logistical advantages. At intermediate temperatures, the oxygen demand of the graft is low enough to be satisfied with an acellular perfusate, obviating the need for oxygen carrying molecules. This intermediate metabolic rate, however, is sufficient to support the production of bile, which is emerging as an important indicator of graft injury and viability. In this study, we hypothesized that the biliary compartment would be more sensitive than perfusate in detecting graft injury during SNMP. Methods. To test this hypothesis in a rat model, we performed liver transplants with DCD and control liver grafts after 1 hr of acellular room temperature machine perfusion (acRTMP) or static cold storage (SCS). Point of care liver function tests were measured in biliary and perfusate samples after 1 hr of machine perfusion. Following transplantation, rats were sacrificed at 24 hr for assessment of post-transplant graft function and histology. Results. All point-of-care liver function tests were significantly more concentrated in the biliary compartment than the perfusate compartment during acRTMP. DCD liver grafts could be distinguished from control liver grafts by significantly higher markers of hepatocyte injury (AST, ALT) in the biliary compartment, but not in the perfusate compartment. Classical markers of cholangiocyte injury, such as gammy-glutamyl transferase (GGT), amylase (AML), and alkaline phosphatase (ALP) were detectable in the biliary compartment, but not in the perfusate compartment. In comparison to SCS, graft preservation by acRTMP produced a significant survival benefit in DCD liver transplantation (75% vs 0%, p<0.0030). Conclusion. Together, these findings demonstrate that during acRTMP, the biliary compartment may be a more sensitive indicator of graft injury than the perfusate. Moreover, acRTMP provides superior graft preservation to SCS in rat DCD liver transplantation.